IMIA – A 40 Year Organizational Overview* - Huesing, S.A. (Yearbook of Medical Informatics, 2007)
To chronicle the history of IMIA, the International Medical Informatics Association, from 1967 to 2007.Describing the key events and accomplishments through the terms of office of its presidents.The IMIA of today has been shaped by the individuals within it. Those influencing and guiding IMIA from its origins to today include its national representatives, Board and Presidents, working group members, regional liaisons, and MedInfo attendees.
Keywords: Medical informatics; health informatics; biomedical informatics; International Medical Informatics Association; IMIA